Media Autonomy in Cross-road in Post-Conflict Democracy of Nepal - Dahal, Sudarshan Prasad (Bodhi: An Interdisciplinary Journal, 2019)
Nepali media intend towards neutral projections of their institutional stance covering politics in a balanced way despite a long practiced political parallelism in the country. The media also project both dark and bright sides of Nepalese politics for strengthening democracy in post-conflict period of Nepal. This study has examined editorial contents covered by two leading Nepali newspapers: The Kathmandu Post daily and Nepali Times weekly, both published in English language. The focus of this research has been to examine the editorials appeared during election campaign of Constitution Assembly, 2008. The study has chosen two dominant framing concepts: thematic vs. episodic framing, in order to explore the phenomenon of media autonomy in the Nepalese context. The findings show a mixed result where the media appear more likely to an instrumentalized phenomenon while projecting government/political parties’ policies and decisions. Their issues and activities were framed thematically putting public issues in general context, and also detracting political issues from negative stereotyping in their institutional viewpoints. At the same time, media portray the issues and activities focusing on particular events and occurrences while framing political parties/governments and their leaders with negative attributes of conflict and personalization frame. It can be argued that some external forces such as increasing dispute among political actors and increasing volume of impunity against journalism could be the consequences of media’s less likely instrumentalized appearance to political forces.